Killing Epsilons with a Dagger: A Coalgebraic Study of Systems with Algebraic Label Structure - Bonchi, Filippo; Milius, Stefan; Silva, Alexandra; Zanasi, Fabio (Theoretical Computer Science, 2015)
We propose an abstract framework for modelling state-based systems with internal behaviour as e.g. given by silent or ε-transitions. Our approach employs monads with a parametrized fixpoint operator † to give a semantics to those systems and implement a sound procedure of abstraction of the internal transitions, whose labels are seen as the unit of a free monoid. More broadly, our approach extends the standard coalgebraic framework for state-based systems by taking into account the algebraic structure of the labels of their transitions. This allows to consider a wide range of other examples, including Mazurkiewicz traces for concurrent systems and non-deterministic transducers.
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.profes_1.killin
Keywords: Coalgebras on kleisli categories; Epsilon transitions; Mazurkiewicz traces; Non-deterministic transducers; Parametrized fixpoint operator; Trace semantics